Anti-noise frequency estimation performance of Hanning-windowed energy centrobaric method for optical coherence velocimeter. (November 2020) - Zhang, Qiukun; Zhong, Shuncong; Lin, Jiewen; Huang, Yuexin; Nsengiyumva, Walter; Chen, Weiqiang; Luo, Manting; Zhong, Jiangfeng; Yu, Yingjie; Peng, Zhike; Cheng, Shuying
Highlights: A calculation method based on Paserval's theorem was proposed to establishes the accuracy theory of Hanning-window energy centrobaric method (HnWECM). The results demonstrate that the variance of the estimated frequency using HnWECM is only proportional to the signal-to-noise ratio (SNR) and very close to the Cramér-Rao Lower Bound (CRLB). The work reveals the reason of chosen HnWECM as the signal processing method of OCV technology and gives its accuracy theory, which will greatly promote the application of OCV technology. Abstract: The Optical Coherence Velocimeter (OCV) technology is a technique for high-precision displacement and vibration measurement based on the principle of spectral domain optical coherence method. The key of this technology is to realize nanometer or even sub-nanometer measurement by high precision frequency estimation method called as Hanning-window energy centrobaric method (HnWECM). This paper analyses the error transmission process of HnWECM, and proposes a calculation method based on Paserval's theorem to establishes the accuracy theory of HnWECM. It shows that the variance of the estimated frequency using HnWECM is only proportional to the signal-to-noise ratio (SNR) and very close to the Cramér-Rao Lower Bound (CRLB). The estimation performance of HnWECM is verified and compared with other frequency estimation methods by simulation and experimental results. Both the theoretical analysis and simulation results show that the HnWECM has good statistical efficiency and the best anti-noise stability. This paper reveals the reason of chosen HnWECM as the signal processing method of OCV technology and gives its accuracy theory, which will greatly promote the application of OCV technology.